PENGARUH PENAMBAHAN ION SULFAT TERHADAP REKOVERI PEMISAHAN URANIUM MENGGUNAKAN METODE KOLOM PENUKAR ANION - Boybul, Boybul; Yanlinastuti, Yanlinastuti; Anggraini, Dian; Ginting, Aslina Br.; Nugroho, Arif; Kriswarini, Rosika (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
In the previous research, it was observed that the recovery of uranium separation by anion exchange column method with HCl 12 N solvent was 68.2137 %. The recovery can be increased by optimizing the uranium separation parameters by the use of HCl and Na2SO4 solvent mixture. A 500 μL uranyl nitrate standard solution was used as feed with varied HCl concentration of 6 N, 9 N, 12 N and varied Na2SO4 concentration of 500, 1000, 1500, 2000, 2500 and 3500 ppm as reagent solution. In the anion exchange process, uranium was bound by the resin to form [UO2(SO4)3]4- and [UO2(SO4)2]2 complex compounds, and these complexes were eluted with 15 mL of 0.15 N HCl dilute solution. The eluate was heated to nearly dried condition and 1 mL of HCl concentrated solution was added for electrodeposition process. The uranium deposited on stainless steel planset, as the result of electrodeposition process, was analyzed with alpha spectrometer. It was observed that the largest 235U content was found in 9M of HCl solvent and 1500 ppm of Na2SO4 with 95.7124 % recovery. Therefore, the concentration value of HCl of 9 N and 1500 ppm of Na2SO4 were subsequently applied to the uranium separation of irradiated U3Si2/Al fuel element plate. An amount of 500 μL supernatant of U3Si2/Al specimen taken from the top, middle and bottom position of fuel element plate (FEP) were put into an anion exchange column containing 1 g of Dowex-Cl resin. The results of the separation process were 235U isotope identified according to their position in the irradiated U3Si2/Al fuel element plate i.e. top, middle, and bottom. It was found that the recovery values were 13265.7866 μg/gFEP; 6923.9248 μg/gFEP; and 12332.4175 μg/gFEP representing their position of top, middle and bottom respectively. It is concluded that the use of 9M of HCl solvent and 1500 ppm of Na2SO4 by anion exchange column method can improve uranium separation recovery from 68.2137 % to 95.7124 %.